2017
DOI: 10.5964/jnc.v3i2.44
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-spatial processes as a domain-general factor impacting numerical development in atypical populations

Abstract: In the past few years, the role of both domain-specific and domain-general factors on numerical development and mathematics achievement has been debated. In this paper, we focus on the role of visuo-spatial processes. We will more particularly review the numerical abilities of populations presenting atypical visuo-spatial processes: individuals with blindness, hemineglect, children presenting low visuo-spatial abilities, non-verbal learning disorder or Williams syndrome. We will show that math abilities of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…Much evidence has suggested the existence of a close link between numbers and space (see Crollen, Collignon, & Noël, 2017;de Hevia, Vallar, & Girelli, 2008, for reviews). Although addition and subtraction operations are assumed to involve movements on the mental number line (Knops et al, 2009;Masson & Pesenti, 2014;McCrink et al, 2007;McCrink & Wynn, 2004Pinhas & Fischer, 2008), and despite the fact that our linear training conditions were left-to-right oriented, we did not find any advantage of the linear training over the random condition.…”
Section: Linear Versus Random Trainingmentioning
confidence: 99%
“…Much evidence has suggested the existence of a close link between numbers and space (see Crollen, Collignon, & Noël, 2017;de Hevia, Vallar, & Girelli, 2008, for reviews). Although addition and subtraction operations are assumed to involve movements on the mental number line (Knops et al, 2009;Masson & Pesenti, 2014;McCrink et al, 2007;McCrink & Wynn, 2004Pinhas & Fischer, 2008), and despite the fact that our linear training conditions were left-to-right oriented, we did not find any advantage of the linear training over the random condition.…”
Section: Linear Versus Random Trainingmentioning
confidence: 99%
“…According to this hypothesis, people deprived of one sensory modality actually develop alternative compensatory sensory and cognitive abilities to process information from the remaining modalities (Collignon, Voss, Lassonde, & Lepore, 2009;Lessard, Pare, Lepore, & Lassonde, 1998;Voss, Lassonde, Gougoux, Fortin, Guillemot, & Lepore, 2004). It was recently suggested that blind people may develop mathematical understanding by mostly relying on haptic manipulation (Crollen, Collignon, & Noël, 2017) or verbal working memory processes (e.g., Castronovo & Delvenne). Interestingly, regions of the occipital cortex that typically process visual information were shown to massively enhance their response to tactile (Reich, Szwed, Cohen, & Amedi, 2011) and verbal information in the blind (Amedi, Raz, Pianka, Malach, & Zohary, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The second aim of the present paper was therefore to study the associations between arithmetic and the 3 WM components in blind children. Indeed, it has been assumed that blind people may compensate for their lack of vision in the development of their arithmetic skills by relying on enhanced WM abilities (Castronovo & Delvenne, 2013;Crollen et al, 2011;Crollen, Collignon, & Noël, 2017;Kanjlia, Feigenson, & Bedny, 2018;Salillas, Granà, El-Yagoubi, & Semenza, 2009) but the three WM components and their links with arithmetic development have never been systematically and directly tested in blind children. We therefore asked our participants to perform several WM tasks and evaluated the relationships between this cognitive function and arithmetic processing.…”
Section: Introductionmentioning
confidence: 99%
“…One first step towards the development of such a taxonomy is taken by Crollen, Collignon, and Noël (2017, this issue) by reviewing findings from several atypical populations with deficits in the visual or visuo-spatial domain:…”
Section: Predicting and Improving Arithmeticmentioning
confidence: 99%